2009
DOI: 10.3109/17477160902923341
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes in youth: A phenotype of poor cardiorespiratory fitness and low physical activity

Abstract: Objective-The increased incidence of obesity and type 2 diabetes (T2D) among youth has prompted the development of guidelines for healthy cardiorespiratory fitness (CRF) and physical activity (PA) levels in the pediatric population. It is unclear whether youth with T2D meet these guidelines as previous research has not included type 2 diabetics. Therefore, the purpose of this investigation was to examine CRF and PA in youth with T2D and compare these results with recently published normative data for CRF and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Physical inactivity, low cardiorespiratory fitness (CRF) [ 1 ] and sedentary behaviour, particularly sitting hours [ 2 ] are primary causal risk factors in the pathogenesis of metabolic disorders amongst children and adolescents. In contrast to the school environment, adolescents are known to self-select higher levels of physical activity throughout a summer vacation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Physical inactivity, low cardiorespiratory fitness (CRF) [ 1 ] and sedentary behaviour, particularly sitting hours [ 2 ] are primary causal risk factors in the pathogenesis of metabolic disorders amongst children and adolescents. In contrast to the school environment, adolescents are known to self-select higher levels of physical activity throughout a summer vacation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“… 6 Current clinical practice guidelines recommend regular daily physical activity for adolescents living with type 2 diabetes. 7–9 Despite these recommendations, our group 10 and others 11 12 demonstrated that adolescents with type 2 diabetes achieve less daily physical activity than their peers without type 2 diabetes. Adolescents without diabetes who engage in regular daily physical activity, 13 particularly vigorous-intensity physical activity, 14 15 display better cardiometabolic profiles compared with adolescents who do not.…”
Section: Introductionmentioning
confidence: 85%
“…8 Furthermore, these low levels of physical activity result in a greater challenge down the road as physical activity is reported to decline from childhood into adolescence. [6][7][8][9][10] The youth most vulnerable to the decline in physical activity tend to be female [9][10][11][12][13][14] or those with obesity or diabetes, [14][15][16][17][18][19] and they are most physically inactive during weekends and outside of school. 13,20 Despite the design and implementation of eloquent physical activity programs aimed at improving and sustaining physical activity adherence, incorporating physical activity as a consistent lifestyle behavior has proven difficult for both youth and adults.…”
Section: Discussionmentioning
confidence: 99%